ChemInform Abstract: Revisiting Ce3Pt4Ge6 — Crystal Structure and Physical Properties. Issue 50 (November 2016) - Janka, Oliver; Hoffmann, Rolf‐Dieter; Eilers‐Rethwisch, Matthias; Rodewald, Ute Ch.; Niehaus, Oliver; Poettgen, Rainer
Abstract: High quality single crystals of Ce3 Pt4 Ge6 are obtained by repeated arc melting of the elements under Ar and subsequent annealing just below the melting point (2 h; slow cooling to 25 °C).